“Who are you working for?”: The role of 24 villains for reinforcing the master narrative of U.S.A history - Gonçalves, Davi (Revista Interfaces, 2023)
The purpose of this article is to analyse some events taking place in the television show 24 as to identify if and how they respond to the master narrative of U.S.A. history, values, and nationalism. More specifically, the study focuses on the depiction of Arab, Russian, and Chinese villains as to analyse how they are constructed and, as such, what these representations might mean. As suggested during the research, 24 seasons and its array of villains impersonating the foreign threat, in parallel with U.S.A. leadership in stopping evil to spread throughout the world, are successful in compressing a political agenda of providing a “young country” with a fixed identity. With the theoretical framework brought by Said (1979), among others, the study identifies how Jack Bauer, the series hero, is not only defined by his actions, but by how they differ from the actions of his antagonists. Interestingly enough, while foreign villains are called fundamentalists due to their religion or blind nationalism, findings demonstrate how the greatest fundamentalist of the series is Bauer himself.